Predicting Attitudes Toward Drugs by Loneliness in University Students in Shiraz - Ghorbanzadeh Korany, Zeinab; sadat mirseifi fard, Leila; Goli, Zahra Sadat; Rahmani Varnamkhasti , Ruhollah (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The objective of this study was to examine the relationship between loneliness and attitudes toward drugs among university students in Shiraz. Specifically, the study aimed to investigate how emotional and social loneliness predict students' attitudes toward substance use, utilizing a cross-sectional design.Methods and Materials: A total of 350 university students from Shiraz were recruited using the sample size determination table by Morgan and Krejcie. Participants completed self-administered questionnaires measuring their attitudes toward drugs and levels of loneliness, assessed using the Attitude to Drug Scale (ADS) and the UCLA Loneliness Scale, respectively. Data were analyzed using SPSS version 27, employing Pearson correlation to explore the relationships between variables and linear regression to determine the predictive power of emotional and social loneliness on drug attitudes.Findings: The results indicated significant correlations between emotional loneliness and negative attitudes toward drugs (r = -0.45, p < 0.001) and between social loneliness and negative drug attitudes (r = -0.32, p < 0.001). Linear regression analysis revealed that both emotional loneliness (β = -0.37, p < 0.001) and social loneliness (β = -0.25, p < 0.001) were significant predictors of negative attitudes toward drugs, with emotional loneliness demonstrating a stronger predictive value. These findings suggest that higher levels of loneliness, particularly emotional loneliness, are associated with more negative attitudes toward substance use among university students.Conclusion: The study concludes that loneliness, especially emotional loneliness, significantly influences university students' attitudes toward drugs. These findings highlight the importance of addressing loneliness in interventions aimed at reducing substance abuse. Universities should implement programs that foster social connections and provide targeted mental health support to mitigate the impact of loneliness on students' drug attitudes.